Employability Social Skills Interventions in Transition-Age Youth with Intellectual Disabilities: A Literature Review - Laskaraki, Eleni; Alevriadou, Anastasia; Rachanioti, Eleni (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Employability skills are necessary for youth with Intellectual Disabilities (IDs) to successfully navigate their transition from educational settings to autonomous adult life. Most importantly, research evidence has shown that individuals with IDs appear to perform adequately on job tasks, yet they frequently face inadequacies in the social aspects of work life. Although much of the existing employability research has focused on social skills training related to employability for individuals with other disabilities, people with IDs are underrepresented in the literature. Thus, this review aimed to provide insight into the existing social skills interventions that promote employability in transition-age youth with IDs. Results indicated that although there is a limited number of studies regarding intervention programs on improving social skills related to employment for individuals with IDs, the majority of them positively impacted target behaviors, thus highlighting the need for further empirical research.